2011
DOI: 10.1002/stem.686
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Human Trophoblast Progenitor Cell Lines from the Chorion

Abstract: Placental trophoblasts are key determinants of in utero development. Mouse trophoblast stem cells (mTSCs), which were first derived over a decade ago, are a powerful cell culture model for studying their self-renewal or differentiation. Our attempts to isolate an equivalent population from the trophectoderm of human blastocysts generated colonies that quickly differentiated in vitro. This finding suggested that the human placenta has another progenitor niche. Here we show that the chorion is one such site. Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 73 publications
3
135
0
Order By: Relevance
“…Role of Activin/Nodal Signaling in Trophoblast Differentiation-It was previously shown that SB431542 treatment leads to trophoblast differentiation (17,33). However, the study was questioned due to the use of ambiguous markers for characterizing hESC-derived trophoblasts (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role of Activin/Nodal Signaling in Trophoblast Differentiation-It was previously shown that SB431542 treatment leads to trophoblast differentiation (17,33). However, the study was questioned due to the use of ambiguous markers for characterizing hESC-derived trophoblasts (43).…”
Section: Discussionmentioning
confidence: 99%
“…2 , embryonic carcinoma cells (30,31), induced pluripotent stem cells (28,32), other multipotent cells (33), and mouse embryonic stem cells (mESCs) (34 -37). Treatment with bone morphogenetic protein (BMP) and/or inhibitors of the activin/nodal pathway have been used for deriving trophoblasts (1, 6 -8, 10, 12-15, 17, 19, 22-29, 33, 38).…”
Section: Trophoblasts Have Been Derived From Human Embryonic Stem Celmentioning
confidence: 99%
“…To obtain transcriptomic profiles of previously isolated trophoblast progenitor cells (TBPC) and human embryonic stem cells (hESC) (Genbacev et al 2011), Affymetrix CEL files were obtained from the National Center for Biotechnology Information's (NCBI) GEO (reference GSE30127). These data were reanalysed using the process described above to obtain a directly comparable set of profiles between the two experiments; in addition, lists of differentially expressed transcripts from this analysis were checked against the analysis in the original publication and found to be in agreement.…”
Section: Transcriptomic Comparison Of Extravillous Trophoblasts Cytomentioning
confidence: 99%
“…It has previously been reported that a TBPC population was isolated from the chorion of first trimester placentae (Genbacev et al 2011). To determine how similar our villus-derived side-population trophoblasts were to this previously published chorionic TBPC population, we reanalysed the data to compare genes that were significantly (P!0.05) up-or down-regulated more than twofold in side-population trophoblasts relative to cytotrophoblasts with genes up-or down-regulated more than twofold in TBPC relative to cytotrophoblasts.…”
Section: Homeobox Array Analysis Suggests Side-population Trophoblastmentioning
confidence: 99%
“…Bipotential trophoblast progenitor cells have been derived from the chorionic mesenchyme differentiating into EVTs and STBs (14,15), whereas others identified a specific precursor of the EVT lineage in villous explant cultures (16). Placental structures, trophoblast cell types, and expression patterns of key regulatory transcription factors diverge between mouse and man, thereby hindering comparison of putative regulatory mechanisms (17).…”
mentioning
confidence: 99%